Trade-offs in Bank Resolution - Dell'Ariccia, Giovanni; Awadzi, Elsie Addo.; Igan, Deniz; Martinez Peria, Maria (Washington, D.C. : International Monetary Fund, 2018)
This SDN revisits the debate on bank resolution regimes, first by presenting a simple model of bank insolvency that transparently describes the trade-off involved between bail-outs, bail-ins, and larger capital buffers. The note then looks for empirical evidence to assess the moral hazard consequences of bail-outs and the systemic spillovers from bail-ins.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet